Economy and Art Why are Economy and Art Closely Linked? - Hasan Alpagu (Journal of Economics Bibliography, 2015)
Most art products can be classified as intangible goods. They characterize a reasonable connection with passion, inspiration, creativity and emotions. However, the pricing of these outcomes is exceptional irregular and uncertain. As a result, the questions arise: What is art? What is the relationship between art and economy? Is there a practical way for artist to be famous and rich at the same time? Why are the fate of the artist depend not only on the quality and creativity of their products, but also to the economic resources? We have taken this phenomenon with particular attention, in which we examine the problem from an economic and artistic point of view.Upon analyzing the relations between art and economy, it provides a comprehensive view about the meaning of artworks for society's economic and cultural development.
Keywords: A00; 330; Art; Economics